ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 55/PUU-XVII/2019 TERKAIT DESAIN PEMILIHAN UMUM SERENTAK GUNA MEWUJUDKAN PENYELENGGARAAN PEMILIHAN UMUM YANG DEMOKRATIS - Silalahi, Elisabeth Felita (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
This research aims to identify and examines issues related to the law interpretation used in the Constitutional Court Verdict Number 55/PUU-XVII/2019 and to analyze the extent to which this verdict has fulfilled the principles of democratic general election in order to formulate an ideal construction model of concurrent election to manifest a democratic election. The type of research in this article is normative or doctrinal and is a descriptive analytical legal research. The result shows that in the Constitutional Court Verdict Number 55/PUU-XVII/2019, the Constitutional Judge in interpreting uses historical and functional interpretation on which is the basis for expanding the meaning of concurrent election into 6 (six) variants of concurrent election design. Thereafter, in the Constitutional Court Decision Number 55/PUU-XVII/2019, there are several variants of concurrent election designs that do not yet fulfill the elements and principles of democratic election management. Based on various studies and considerations, it is necessary to reconstruct the concurrent election model through the division of national concurrent election and local concurrent election.Keywords : Constitutional Court Verdict Number 55/PUU-XVII/2019, Concurrent Election, Interpretation, Democratic Election